Anti-inflammatory and antinociceptive effects of active ingredients in the essential oils from Gynura procumbens, a traditional medicine and a new and popular food material. (15th July 2019) - Huang, Xia-Ling; Li, Xiao-Jun; Qin, Qiu-Fang; Li, Yu-Sang; Zhang, Wei Kevin; Tang, He-Bin
Abstract: Ethnopharmacological relevance: Gynura procumbens is applied topically for the treatment of traumatic injuries in South China. Materials and methods: This study was conducted to identify the active ingredients in the essential oils from Gynura procumbens (GPEO) by Gas Chromatography-Mass Spectrometer (GC–MS) and to elucidate the mechanisms underlying the anti-inflammatory and antinociceptive effects in vivo and in vitro . Results: A reduction in dswelling and pain were observed in mice treated with GPEO or its active ingredients (α-pinene, 3-carene, and limonene) compared with mice treated with a solvent control. GPEO or its three active ingredients had potent pharmacological effects on COX-2 overexpression and LPS-induced migration of Raw264.7 macrophages. All three ingredients inhibited nociceptive stimulus-induced inflammatory infiltrates and COX-2 overexpression, which could be responsible for the anti-inflammatory effect of GPEO. However, only 3-carene produced an antinociceptive effect. Conclusion: Consistent with the traditional usage in Southern China, GPEO may serve as a promising potent external therapeutic agent for the treatment of chronic pain. Graphical abstract: Image 1